Pisarz w archiwum. Prace nad poznańskim Archiwum Włodzimierza Odojewskiego - Przybyszewska, Alicja; Nowakowska, Dagmara (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article is a collection of thoughts that transpired during the work at the Archive of Włodzimierz Odojewski. The aim of the authors was to identify and indicate the potential ways to study the life and works of the writer, and the expected result of the research is a biography of Odojewski. The research was based on the exploration of the writer’s private collection: unpublished documents, manuscripts, typescripts, personal papers, correspondence, family and estate papers and photographs. The authors focused on a number of issues. One, the biographical facts that influenced Odojewski’s output – World War II, frequent relocations, censorship and a ban on publishing in Poland, emigration, the relation with the Polish Institute in Maisons-Laffitte and working at Radio Free Europe’s editorial office. Two, the analysis of literary works including hundreds of typescripts in many variants (related to the phases of the genetic history of a literary work through the stages of Odojewski’s life) which allowed for describing Odojewski’s writing techniques. Three, ‘The writer’s map’ which points out places important for the author – Poznań, Gniezno, Kłecko, Podole, Szczecin, Warsaw, Paris, Berlin, Munich. Four, the correspondence (personal and cultural) which can be used as an important source of knowledge of the history of Polish post-war emigration. One of the most interesting parts of the collection is a collection of letters from Jerzy Giedroyć that show Polish culture outside the Iron Curtain.